2009
DOI: 10.1073/pnas.0908176106
|View full text |Cite
|
Sign up to set email alerts
|

Reelin signaling antagonizes β-amyloid at the synapse

Abstract: Abnormal processing of the amyloid precursor protein (APP) and ␤-amyloid (A␤) plaque accumulation are defining features of Alzheimer disease (AD), a genetically complex neurodegenerative disease that is characterized by progressive synapse loss and neuronal cell death. A␤ induces synaptic dysfunction in part by altering the endocytosis and trafficking of AMPA and NMDA receptors. Reelin is a neuromodulator that increases glutamatergic neurotransmission by signaling through the postsynaptic ApoE receptors Apoer2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(144 citation statements)
references
References 38 publications
4
138
0
Order By: Relevance
“…Activation of Reelin signaling at the synapse can prevent β-amyloid-induced LTP suppression (13). To test ability of Reelin to maintain normal hippocampal LTP in the presence of naturally occurring oligomeric Aβ, we perfused hippocampal slices from the different ApoE knockin mice with ACSF containing either brain extract from a human non-AD case (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of Reelin signaling at the synapse can prevent β-amyloid-induced LTP suppression (13). To test ability of Reelin to maintain normal hippocampal LTP in the presence of naturally occurring oligomeric Aβ, we perfused hippocampal slices from the different ApoE knockin mice with ACSF containing either brain extract from a human non-AD case (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aβ oligomers potently suppress synaptic functions and impair synaptic plasticity (reviewed in ref. 21), and we have recently shown that Reelin signaling through Apoer2 can prevent the Aβ oligomer-induced inhibition of NMDA receptors at the synapse (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential mechanisms by which ApoE receptors may promote neuronal survival (Beffert et al 2006b) during aging involve signaling pathways that control microtubule and actin dynamics Assadi et al 2003;Brich et al 2003;Ohkubo et al 2003;Chai et al 2009;Forster et al 2010;Rust et al 2010), dendritogenesis (Niu et al 2004), spine formation (Niu et al 2008), glutamate receptor function and synaptic plasticity (Zhuo et al 2000;Weeber et al 2002;Beffert et al 2005;Chen et al 2005;D'Arcangelo 2005;Sinagra et al 2005;Groc et al 2007;Durakoglugil et al 2009;Korwek et al 2009;Chen et al 2010), as well as learning and memory (reviewed in Herz and Beffert 2000;Herz and Chen 2006;Bu 2009;Herz 2009). In this section we will mainly focus on the role of the ApoE receptors Apoer2 and Vldlr and their ligand Reelin in these processes.…”
Section: Apoe Receptors and Synaptic Plasticitymentioning
confidence: 99%
“…Moreover, Reelin signaling activates SFKs , which would directly oppose the activity of the phosphatases on the NMDA receptor (Snyder et al 2005). This hypothesis was tested by measuring the effect of different Ab preparations, including Ab-containing extracts from human AD brain, on hippocampal synaptic plasticity, NMDA receptor tyrosine phosphorylation, and activity in response to Reelin (Durakoglugil et al 2009). At low to intermediate, but not at unphysiologically high (.400 nM) Ab concentrations, activation of Reelin signaling can completely prevent the synaptic suppression induced by the oligomers, suggesting that Reelin is a physiological mediator of neuroprotection.…”
Section: Apoe Receptors As Antagonists Of Ab-induced Synaptic Suppresmentioning
confidence: 99%